Nationwide Trends in Reperfusion Therapy and Outcomes of Acute Ischemic Stroke According to Severity: The Japan Stroke Data Bank - Junpei Koge; Sohei Yoshimura; Masatoshi Koga; Michikazu Nakai; Shinichi Wada; Yusuke Sasahara; Masayuki Shiozawa; Kaori Miwa; Akiko Ishigami; Kazutaka Sonoda; Koji Iihara; Fusao Ikawa; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Background It is unclear whether all patient subgroups with acute ischemic stroke have benefited from advances in reperfusion therapy. We investigated long‐term trends of reperfusion therapy and outcomes according to the stroke severity. Methods Patients with acute ischemic stroke registered in the prospective nationwide hospital‐based registry between 2000 and 2020 were examined. Baseline National Institutes of Health Stroke Scale (NIHSS) score ≥10 and ≤5 was considered to indicate possible large vessel occlusions and minor deficits, respectively. Secular changes were assessed per 5‐year cohorts (2000–2005, 2006–2010, 2011–2015, 2016–2020). Outcomes included favorable outcome (modified Rankin scale score 0–2 at discharge). Results Of 127 741 patients, NIHSS score was ≥10 in 31 747 patients (24.9%), 6–9 in 17 083 patients (13.4%), and ≤5 in 78 911 patients (61.8%). In patients with NIHSS score ≥10, intravenous thrombolysis frequency increased from 1.6% to 26.5% between the 2000 to 2005 and 2016 to 2020 cohorts; endovascular therapy frequency increased from 2.0% to 29.8%. Favorable outcomes increased over time (adjusted odds ratio per 1‐cohort, 1.254 [95% CI, 1.204–1.306]). In patients with NIHSS score 6–9, intravenous thrombolysis frequency increased from 0.5% to 16.4%, and endovascular therapy frequency increased from 1.1% to 9.0%. Favorable outcomes did not change over time (1.005 [0.966–1.046]). In patients with NIHSS score ≤5, intravenous thrombolysis frequency increased from 0.2% to 5.1%, and endovascular therapy frequency increased from 0.7% to 2.8%. Favorable outcomes decreased over time (0.954 [0.931–0.978]). Conclusions Use of reperfusion therapy has increased, particularly in patients with NIHSS score ≥10. Favorable outcomes significantly increased over time in patients with NIHSS score ≥10 but decreased in those with NIHSS score ≤5.